Pengaruh Eksrak Daun Binahong (Anredera cordifolia (Ten.) Steenis) Terhadap Pertumbuhan Bakteri Streptococcus pyogenes Secara In Vitro - Yuliana Prasetyaningsih (LPPM STIKES Guna Bangsa Yogyakarta, 2017)
Background: Infectious diseases are diseases caused by pathogenic bacteria such as Streptococcus pyogenes bacteria. This bacterium is a gram-positive, cocci-shaped chain that infect the respiratory tract. As a result of irrational use of antibiotics is causing bacterial resistance. Utilization of plants used in traditional medicine as an alternative by some people. Binahong (Anredera cordifolia (Ten.) Steenis) is a plant that can be used as a traditional medicine can be found easily in Indonesia. Binahong is one of the medicinal plants are thought to have antibacterial effects.